2016
DOI: 10.1038/modpathol.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling identifies decreased expression of miR-205 in inflammatory breast cancer

Abstract: Inflammatory breast cancer is the most aggressive form of breast cancer. Identifying new biomarkers to be used as therapeutic targets is in urgent need. Messenger RNA expression profiling studies have indicated that inflammatory breast cancer is a transcriptionally heterogeneous disease, and specific molecular targets for inflammatory breast cancer have not been well established. We performed microRNA expression profiling in inflammatory breast cancer in comparison with locally advanced noninflammatory breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 89 publications
3
15
0
Order By: Relevance
“…Indeed, miR-205-5p expression decreased with the tumor stage from Elston histological grade I through III (Fig 3), where grade III indicates tumor aggressiveness and patient poor survival [13]. Similar results were also observed in other clinical breast cancer cohorts where miR-205-5p expression levels were measured by qRT-PCR [25, 26] and by in situ hybridization [27]. In addition to the miR-205-5p downregulation in high grade tissue biopsies, the presence of blood circulating miR-205-5p, indicating an overall high expression correlated with tumor chemo sensitivity and higher rates of disease free survival [28].…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, miR-205-5p expression decreased with the tumor stage from Elston histological grade I through III (Fig 3), where grade III indicates tumor aggressiveness and patient poor survival [13]. Similar results were also observed in other clinical breast cancer cohorts where miR-205-5p expression levels were measured by qRT-PCR [25, 26] and by in situ hybridization [27]. In addition to the miR-205-5p downregulation in high grade tissue biopsies, the presence of blood circulating miR-205-5p, indicating an overall high expression correlated with tumor chemo sensitivity and higher rates of disease free survival [28].…”
Section: Discussionsupporting
confidence: 65%
“…A large number of genes are associated with the development and progression of breast cancer, such as the mutation of phosphatase and tensin homolog (PTEN) (6), tumor protein p53 (TP53) (5), matrix metalloproteinase 1 (MMP1) (7) and vascular endothelial growth factor (VEGF) (7). miRNAs are small (~22 nucleotides) non-coding RNAs with generegulatory functions which act by binding to the 3'untranslated region of their target mRNA, resulting in either repression of translation or mRNA degradation (8). miRNAs are remarkably tissue specific and have been used to identify the tissue in which cancer of unknown primary origin arose (9).…”
Section: Conclusion: Our Findings Provide a Functionally Coordinated mentioning
confidence: 99%
“…Poor survival outcomes have prompted investigation into potential unique features of IBC that distinguish it from other types of invasive breast cancer. Some have suggested that IBC is a distinct biological subtype that transcends the standard approximated biological subtype classification based on oestrogen receptor (ER) and HER2 expression that is used to guide treatment and inform prognosis for the more common types of invasive breast cancer.…”
Section: Introductionmentioning
confidence: 99%